Antenatal Diagnosis of Pulmonary Sequestration: A Case Report - Kaushik, Gaurav; Shelar, Rohan; Bangde, Pratik (Asian Journal of Medical Radiological Research, 2021)
Pulmonary sequestration is an uncommon medical condition in which a lung tissue is formed, which does not perform any function and also is not either the other anatomical structures of the main lung tissue, not its blood supply. A 28 years old antenatal mother, visited our department for routine anomaly scan in her second trimester. Transabdominal ultrasound examination revealed a well-defined echogenic mass involving the left hemi-diaphragm extending upwards towards the lung. Colour Doppler study revealed feeding artery which originated from the descending thoracic aorta. This confirmed our diagnosis of pulmonary sequestration. A male baby, weighing 3150 grams was delivered vaginally. High Resolution Computed Tomography showed evidence of a large well defined soft tissue mass involving the left pleural cavity with pleural effusion, and shift of mediastinum and heart towards the right side. In addition, there was an evidence of a feeder artery which originated from the descending thoracic aorta.